Angola : Public Expenditure Review, Volume 2. Sectoral Review - World Bank; European Commission; Food and Agriculture Organization; United Nations Children’s Fund; United Nations Development Program; World Health Organization (Washington, DC, 2012)
This report concerns about policy briefing and outlines the main findings and policy options associated with the analysis of public spending in terms of equity and allocative efficiency. This Public Expenditure Review (PER) covers the sectors of Education, Health, Agriculture, and the area of decentralization. The main objective of this Public Expenditure Review is to examine the allocative efficiency and equity of public spending in Angola. Five cross-cutting messages are drawn from the analysis of public spending and fiscal management in the context of this Public Expenditure Review: (i) the need to prepare public spending plans within a multiyear perspective; (ii) the need to improve the efficiency of public spending; (iii) the need to improve the quality of the data on social indicators and on the budget; (iv) the need to observe equity considerations in the preparation of the budget ; and (v) the need for steady progress with decentralization. The first volume, a policy briefing, outlines the main findings and policy options associated with the analysis of public spending in terms of equity and allocative efficiency. The second volume presents a fuller assessment of each sector and on decentralization